Impact of the pandemic on digital management: a bybliometric analysis - Shagyrbay, Aidana; Ashirbekova, Laura (Farabi Journal of Social Sciences, 2021)
Abstract Digital management is developing every year. The number of studies related to digital management is also increasing. Digital management contributes to the development of new markets and sectors of the economy, stimulates innovation and ensures productivity growth. It also brings significant changes to the organization, its processes and all areas. Using tools and trends in digital management, many foreign organizations are making great strides. In the context of continuous information development, managers need to process large volumes of external information and use digital governance tools to stay on top of innovation. The use of digital management tools opens up new opportunities for all organizations and allows to create business processes taking into account an actively changing environment. Currently, we can observe how digital transformation is taking place in all areas. The purpose of this research work is to conduct a bibliographic analysis of the digital management literature. The research consists of two stages: descriptive – bibliographic analysis and content analysis. The research work analyzes and compares studies conducted in 2017-2019 and 2020-2021 related to digital management. A review of digital management research based on Scopus is carried out. In general, 1682 studies in the field of digital management were analyzed for 2020-2021. Their indicators were described by the program VosViewer. In addition, the worldwide pandemic has also had a significant impact on the development of digital management. In this regard, 49 conducted research works were identified. In the future, digital management research still needs to be deeply studied. Key words: digital management, digital transformation, digital technologies, COVID-19.